2013
DOI: 10.1111/ceo.12200
|View full text |Cite
|
Sign up to set email alerts
|

Ibopamine challenge test can be used to differentiate glaucoma suspects from glaucoma patients

Abstract: This study demonstrates that ibopamine has potential as a test to differentiate glaucoma suspects from patients with glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
1
11
1
1
Order By: Relevance
“…The ability of the ibopamine test result in discriminating between converters and non-converters was very poor, with a sensitivity of 69% and a specificity of 41.4%, suggesting that a large proportion of the OHT subjects had a reduced outflow of the aqueous humor. Although several previous authors have demonstrated that the ibopamine test has high accuracy in differentiating glaucomatous eyes from normal 46 and glaucoma suspect eyes, 47 our data show that the positivity of the ibopamine test has no predictive value for the development of glaucoma. The results of the present study suggest that the ibopamine provocative test seems to be efficient in indicating the actual health status of the trabecular meshwork, but it seems unable to predict the evolution of the glaucomatous disease.…”
Section: Discussioncontrasting
confidence: 99%
“…The ability of the ibopamine test result in discriminating between converters and non-converters was very poor, with a sensitivity of 69% and a specificity of 41.4%, suggesting that a large proportion of the OHT subjects had a reduced outflow of the aqueous humor. Although several previous authors have demonstrated that the ibopamine test has high accuracy in differentiating glaucomatous eyes from normal 46 and glaucoma suspect eyes, 47 our data show that the positivity of the ibopamine test has no predictive value for the development of glaucoma. The results of the present study suggest that the ibopamine provocative test seems to be efficient in indicating the actual health status of the trabecular meshwork, but it seems unable to predict the evolution of the glaucomatous disease.…”
Section: Discussioncontrasting
confidence: 99%
“…In the analysis of 18 glaucoma suspects and 21 patients with glaucoma, ibopamine showed the potential to differentiate between them [29]. In fact, an increase of IOP of 1.9±1.6 mmHg (12.5±10.3%) was observed for glaucoma suspects, whereas the corresponding figure for glaucoma patients was 7.4±4.0 mmHg (52.4±26.5%; p<0.0001).…”
Section: Provocative Testmentioning
confidence: 91%
“…It has been consistently shown that the instillation of ibopamine 2% results in a marked (up to 92%) increase of IOP in eyes with open-angle glaucoma, while no such effect is reported in healthy eyes [3,9,18,28,29,30]. This dose-dependent effect reaches its peak within 45 minutes from the first instillation and lasts about 180 minutes, without any painful symptom or ocular discomfort [18].…”
Section: Provocative Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The instillation of ibopamine increases the IOP only in about 96% of eyes with POAG [8,9,10] (Figures 2, 3). In normal eyes, 2% ibopamine does not significantly affect IOP, with a possible mild hypotensive effect (1-2 mmHg) (Figure 4).…”
Section: Pathophysiology Of Iopmentioning
confidence: 98%